The effect of seasonal food restriction on the metabolism and circadian activity of the South African hedgehog Erinaceus frontalis (: Insectivora) - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2022)
Thesis (BSc (Hons))--University of Pretoria, 1989.